The Role of Positive and Negative Information Processing in COVID-19 Vaccine Uptake in Women of Generation X, Y, and Z: The Power of Good is Stronger Than Bad in Youngsters? - Marschalko, Eszter Eniko; Szabo, Kinga; Kotta, Ibolya; Kalcza-Janosi, Kinga (Frontiers in Psychology, 2022)
Background: Positive and negative focus in information processing associated with age has a diverse role in COVID-19 vaccine uptake. The aim of the study was the exploration of the generational diversity among psychological predictors of COVID-19 vaccine uptake. Methods: A cross-sectional research was conducted. The sample included 978 Hungarian women. Based on former literature findings, the COVID-19 vaccine uptake predictors were chosen from the health beliefs model, Covid-19 vaccine hesitancy and psychological flexibility. Multivariate logistic regression analysis was conducted to investigate the predictors of COVID-19 vaccine uptake in women of Gen X, Gen Y and Gen Z. Results: In Gen X women, the influence of significant predictors are more prone to the positivity in COVID-19 vaccine uptake behavior, perceived benefits being the most relevant, increasing the likelihood of vaccine uptake more than 4 times. In Gen Y women, perceived barriers, lack of confidence/ skepticism and avoidance significantly reduce the probability of vaccine uptake, showing an accentuated negative focus in information processing related to COVID-19 vaccination. The vaccine uptake in Gen Z is predicted only by the perceived benefits, and the likelihood of COVID-19 vaccine uptake is heightened in chance more than 19 times. Conclusions: For Gen X and Y women, the perceived benefits hold the key to vaccine uptake, while in women of Gen Y, low risks, lack of threats and accessibility could motivate the decision of vaccine uptake. The findings are useful in generation adapted vaccination campaigns and can also serve as inspiration for evolutionary psychology studies on health behavior and for the broad area of study in cognitive biases in health information processing.